Implementation of Constructivism-Based Game-Based Learning Model in Science Learning for Grade IV - Prayogi, Oky; Dwi Puspita, Ryan (PPG IKIP Siliwangi, 2025)
This study aims to describe the implementation of a Game-Based Learning model grounded in constructivist theory in the teaching of Science and Social Studies (IPAS) in fourth-grade elementary school classrooms. This descriptive research explores the learning process that incorporates educational games to foster students’ active engagement in constructing conceptual understanding. The participants of this study were fourth-grade teachers and students at SDN 6 Metro Pusat. Data collection techniques included observation and interviews. The findings indicate that the use of Game-Based Learning enhances student participation in learning activities, promotes collaboration, and strengthens conceptual understanding through real-life learning experiences. Data presentation shows that 83% of students expressed agreement with the constructivism-based Game-Based Learning approach, categorized as forceful. In addition, teacher interviews revealed a score of 79%, categorized as strong. Thus, the constructivist-based Game-Based Learning approach has been proven to create an enjoyable learning environment and stimulate students' intrinsic motivation. These findings suggest that the implementation of educational games integrated with a constructivist approach has the potential to be an effective learning strategy to improve the quality of IPAS education in elementary schools